Assessment of strengthening solutions for the out-of-plane collapse of masonry infills through textile reinforced mortars - Maria Teresa de Risi (2019)
Out-of-plane (OOP) collapse of infill masonry walls in existing reinforced concrete (RC) buildings due to earthquakes represents a paramount issue for life safety and seismic economic loss estimation. Few studies from literature deal with this topic, particularly regarding possible strengthening strategies to prevent the infills' OOP collapse. This work presents the first results of a proper experimental campaign about the assessment of different strengthening solutions designed to mitigate or avoid the out-of-plane collapse of masonry infills in existing RC buildings. The investigated strengthening techniques were based on the application of a very thin high-ductility mortar plaster and glass fibre-reinforced polymer nets with different types of anchorage to the surrounding RC frame. Each specimen was built with horizontal hollow clay bricks and was tested through the application of a semi-cyclic OOP displacement pattern by means of uniformly distributed small pneumatic jacks. Mechanical properties of the adopted materials, test setup and procedure are described herein. Tests results are presented and commented in terms of OOP force-displacement responses and damage evolution during the test. Details about the effectiveness of each retrofitting solution are provided and compared to support the selection of the best strategy for further investigations and future applications.